THE IMPACT OF PUBLIC INVESTEMENT CONSUMPTION AND GPD IN POLAND 1995-2018 ON THE SME DEVELOPMENT (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of the research contained in this publication is to determine the mutual response to the impulse of public investment, consumption and GDP in the years 1995-2018 in Poland. Through empirical research on a quarterly basis with the use of the Gretl program, the validity of the hypothesis of pushing private capital into the economy as a pull reaction to public investment in Poland for 1996-2018 was analyzed. The analyzed investments have a particularly positive effect on small and medium-sized economic entities as they are more connected with local markets.